(untitled) (Research, Society and Development, 2022)
Feminicides are not distributed randomly, they are the product of a convergence of social, political, economic and cultural factors that come together to cause violent events to happen in the territory. The aim of the present study is to analyze the spatial distribution of the risk of death from femicide in the city of Campinas, São Paulo - Brazil through a case-control study. Trained researchers collected information from the cases using the technique of verbal autopsy. During 2018 and 2019 there were 24 cases of femicide. Female victims died mainly in their homes as a result of attacks with sharp objects provided mainly boyfriends and spouses. Cases were distributed across the territory and paired with city controls in a 1:4 ratio. A spatial analysis was carried out identifying the places of residence and death of female victims. Using a generalized linear model, the northwest and southwest regions of the city were determined as those in which there is a greater risk of occurrence of cases. The findings are discussed within the framework of Brazilian legal normativity and the intervention axes for the elimination of lethal violence against women in the Latin American context.